Communication Ethics on Social Media in the Perspective of Hadith in the Digital Era - Haerudin Haerudin; Abdul Kholik; Rahma Dilla Zainuri; Agus Fudholi; Bayu Priyatna (Attractive : Innovative Education Journal, 2026)
This research is motivated by the rampant ethical crisis on social media, such as the spread of hoaxes, cyberbullying, hate speech, and privacy violations (doxing). Today's digital phenomenon often prioritizes the speed of information dissemination over accuracy and benefits, which has an impact on moral degradation and social polarization. In fact, the formal legal apparatus has not been fully able to touch the deepest moral awareness of internet users. Therefore, the purpose of this study is to formulate a guide to digital communication ethics based on the hadiths of the Prophet Muhammad PBUH as a preventive instrument for social media users. The research method used is qualitative with the type of library research. Data sourced from primary hadith books and supporting literature that were analyzed using content analysis techniques and normative-theological approaches to relate religious texts to modern communication phenomena. The results of the study show that there are six pillars of digital communication ethics in hadith: the obligation to verify information (tabayyun), responsibility for the impact of messages, ensuring the safety of fellow users from cyber disturbances, protection of privacy/disgrace of others, the principle of self-control through speaking well or silently, and the prohibition of the use of abusive words and curses. The implementation of these six hadiths serves as a transformative moral filter for the user's character. In conclusion, the integration of hadith values in digital activities is crucial to create social harmony and ensure the spiritual safety of users in the midst of a tsunami of information. This nubuwah ethics provides a visionary solution for the creation of a healthy, safe, and dignified social media ecosystem.